2001
DOI: 10.1046/j.1365-2648.2001.01983.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental disturbances and perceived complexity of nursing care in medical inpatients: results from a European study

Abstract: Mental disturbances and perceived complexity of nursing care in medical inpatients: results from a European study Aims and objectives. The relationship between mental disturbances – anxiety and depression, somatization and alcohol abuse – on admission to internal medicine units and perceived complexity of care as indicated by the nurse at discharge was studied. The goal was to study the utility of short screeners for mental disturbances to select patients for case‐management on admission. Design. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…2005, Allareddy & Konety 2006, Odetola et al. 2007) and poor mental health status on admission (De Jonge et al. 2001) impact complexity of care and utilisation of service, thereby affecting system cost outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…2005, Allareddy & Konety 2006, Odetola et al. 2007) and poor mental health status on admission (De Jonge et al. 2001) impact complexity of care and utilisation of service, thereby affecting system cost outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…De Jonge et al. (2001) evaluated perceived care complexity of patients hospitalized in general hospitals across Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of this simple screener to detect early patients at risk for complex care in the respiratory ward should be stressed. Authors in our workgroup have reported that early detection followed by a relatively simple intervention could greatly reduce healthcare use (de Jonge et al. 2001a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Cochran's coefficient was selected for this, since it is more stringent than inter-rater reliability coefficients in instruments with a yes/ no answering system such as COMPRI. Furthermore, in relation to the instrument itself, while de Jonge et al (2001b) have expressed some concerns about using subjective ratings of care complexity by physicians and nurses, they have also shown that the potential limitation is overcome by COMPRI's power for prediction. Finally, following methods for the validation of the original version, COMPRI was completed in this study by a research nurse.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation